Payroll System Analysis in Culinary Business: Case of Kedai Pek Kau 89 Rungkut Madya - Surabaya - Putri, Gressia Clara Vandika; Martha, Nissa Sabilia; Putri, Faridatun Nisa’ Ramadhani; Fahriya, Naura Indri; Utomo, Zenedine Camelia (PT Global Digital Sains Tekno, 2025)
Purpose: This study aims to examine the implementation of the payroll and wage system at Kedai Pek Kau 89 Pangsit Mie Ayam, a small business in the culinary sector, and to identify existing weaknesses that may affect employee motivation, satisfaction, and operational performance. The study focuses on how payroll systems influence not only timely compensation but also the overall trust and well-being of employees in a small-scale business setting. Method: A descriptive research design with a qualitative approach was used in this study. Data were collected through in-depth interviews and direct field observations with the owner and employees to explore the current payroll practices and internal control mechanisms implemented in the business. Findings: The findings show that the existing payroll system is not fully aligned with proper internal control standards. One of the critical issues identified is the ineffective monitoring of employee attendance, which results in inaccurate salary calculations, employee dissatisfaction, and reduced morale. These deficiencies also contribute to inefficiencies in payroll processing and may hinder the long-term performance of the business. Implication: These results underline the need for a more structured internal control system, particularly in the area of attendance tracking and documentation practices. Implementing these improvements can help ensure fair and accurate salary distribution, improve employee satisfaction, and promote a more efficient and sustainable operation. Originality: This study provides original insights by exploring payroll system challenges in a small culinary business a context that is underrepresented in current research. It also offers practical recommendations that can serve as a reference for similar micro and small enterprises facing comparable payroll issues.